Delayed penile prosthesis implantation in the delayed presentation of ischemic priapism - Mohamed, IRZI; Tarik, MHANNA; Amine, EL HOUMAIDI; Aynaou, Mohammed; Chennouf, Mehdi; Abdelghani, OURAGHI; Wassim, ALAOUI MHAMMEDI; Barki, Ali (Archives of Case Reports, 2020)
Priapism is currently defined as a prolonged painful erection without sexual stimuli, if priapism persists > 36 hours, conservative treatment does not lead to detumescence. The most common etiologies are: medications into corpora cavernosa, anti-psychotics, anti-hypertensives, hematological disorders (chronic myeloid leukemia). The Penile prosthesis is the choice treatment for restoring the erectile function after the failure of the conservative treatment. But the corporal fibrosis makes it very difficult, with high risk of complications [1].